SOLUTION
A conic with center, vertex and focus is an Elispse
Write out the givencoordinates
![\begin{gathered} \text{center}=(-7,-3) \\ \text{vertex}=(-7,4) \\ \text{Focus =(-7,3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sa8ldd05x74qfovc9xgz7oortjteuv1xdz.png)
Since the x-coordinate of the given vertices and foci are the same, the equation becomes
![(\mleft(x-h\mright)^2)/(b^2)+((y-k)^2)/(a^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/n9f5jccdhj0jibial58iz8apefca6zdu80.png)
Where
![\begin{gathered} \text{The center is (h,k) coordinates of the center } \\ \text{hence } \\ h=-7,k=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eek26ukeh1vgk5gqg2yhkojo31t036gsgt.png)
Then
![\begin{gathered} \text{The vertices are } \\ (-7,4)\text{ and the other vertex is } \\ (-7,-10) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yzmpcy500cjs8kscj0hfh7jhiyvummljk0.png)
Hence
![\begin{gathered} \text{Distance betw}en\text{ the two given} \\ 4-(-10)=4+10=14 \\ \text{Then} \\ 2a=14 \\ a=(14)/(2)=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nbs4ogtbmbhvz1yki6g3n4f6dkd2q3hbq7.png)
Then
From the given coordinates of the focus (h,k±c) and center (h,k)
![\begin{gathered} \text{focus =(-7,3)} \\ \text{Center}=(-7,-3) \\ \text{then } \\ K=-3, \\ K+C=3 \\ \text{Then} \\ -3+C=3 \\ C=3+3=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/voxoek9ijhm2qrq8qio5ln0qxwre3x4zpp.png)
hence
![\begin{gathered} a=7,a^2=7^2=49 \\ c=6^2,c^2=6^2=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/61m6vt3v9xlgx8lrbvr8cdzpdz16hq971f.png)
Using
![\begin{gathered} c^2=a^2-b^2 \\ \text{Substitute the value } \\ 36=49-b^2 \\ 36-49=-b^2 \\ \text{Multiply throught by -1} \\ b^2=49-36 \\ b^2=13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vx7e029mlpfvc7mlgamasi6r6fdijagvdl.png)
Recall the standard equation as
![\begin{gathered} ((x-h)^2)/(b^2)+((y-k)^2)/(a^2)=1 \\ h=-7,k=-3,b^2=13,a^2=49 \\ \text{Then } \\ ((x-(-7))^2)/(13)+((y-(-3))^2)/(49)=1 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y6wjxhzu00064fz08x4xl3qhvop7xazm8m.png)
Therefore
The standard equation becomes
![((x+7)^2)/(13)+((y+3)^2)/(49)=1](https://img.qammunity.org/2023/formulas/mathematics/college/7kicci6ip7jjecdh764q6epsr78jfcy51t.png)
Therefore the standard equation is of the conic is (x+7)²/13 + (y+3)²/49=1